Ethical Practice Under Accountable Care - Graber, Abraham D. (HEC Forum, 2016)
Accountable Care Organizations (ACOs) are a key mechanism of the Patient Protection and Affordable Care Act (PPACA). ACOs will influence incentives for providers, who must understand these changes to make well-considered treatment decisions. Our paper defines an ethical framework for physician decisions and action within ACOs. Emerging ethical pressures providers will face as members of an ACO were classified under major headings representing three of the four principles of bioethics: autonomy, beneficence, and justice (no novel conflicts with non-maleficence were identified). Conflicts include a bias against transient populations, a motive to undertreat conditions lacking performance measures, and the mandate to improve population health incentivizing life intrusions. After introducing and explaining each conflict, recommendations are offered for how providers ought to precede in the face of novel ethical choices. Our description of novel ethical choices will help providers know what to expect and our recommendations can guide providers in choosing well.